THE ROLE OF FINANCIAL RESOURCES IN IMPROVING THE QUALITY OF ECONOMIC GROWTH: THE CASE OF UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2026)
This article analyzes the impact of financial resources on the quality of economic growth using the example of Uzbekistan. In the current environment, although many developing countries are achieving high rates of economic growth, the issue of improving its quality is becoming increasingly urgent. From this point of view, the issues of effective distribution and rational use of financial resources - investments, bank loans, government spending and foreign direct investment - are studied. At the same time, it was found that not all types of financial resources affect the quality of economic growth to the same extent. This indicates the need to improve the efficiency of financial resource management and institutional factors. Based on the results of the study, practical proposals were developed aimed at the targeted allocation of financial resources, increasing financial inclusion, and ensuring sustainable economic growth.